Nf1 deficiency modulates the stromal environment in the pretumorigenic rat mammary gland - Arumugam, Menusha; Tovar, Elizabeth A.; Essenburg, Curt J.; Dischinger, Patrick S.; Beddows, Ian; Wolfrum, Emily; Madaj, Zach B.; Turner, Lisa; Feenstra, Kristin; Gallik, Kristin L.; Cohen, Lorna; Nichols, Madison; et al. (Frontiers in Cell and Developmental Biology, 2024)
BACKGROUND: Neurofibromin, coded by the NF1 tumor suppressor gene, is the main negative regulator of the RAS pathway and is frequently mutated in various cancers. Women with Neurofibromatosis Type I (NF1) -a tumor predisposition syndrome caused by a germline NF1 mutation -have an increased risk of developing aggressive breast cancer with poorer prognosis. The mechanism by which NF1 mutations lead to breast cancer tumorigenesis is not well understood. Therefore, the objective of this work was to identify stromal alterations before tumor formation that result in the increased risk and poorer outcome seen among NF1 patients with breast cancer. APPROACH: To accurately model the germline monoallelic NF1 mutations in NF1 patients, we utilized an Nf1-deficient rat model with accelerated mammary development before presenting with highly penetrant breast cancer. RESULTS: We identified increased collagen content in Nf1-deficient rat mammary glands before tumor formation that correlated with age of tumor onset. Additionally, gene expression analysis revealed that Nf1-deficient mature adipocytes in the rat mammary gland have increased collagen expression and shifted to a fibroblast and preadipocyte expression profile. This alteration in lineage commitment was also observed with in vitro differentiation, however, flow cytometry analysis did not show a change in mammary adipose-derived mesenchymal stem cell abundance. CONCLUSION: Collectively, this study uncovered the previously undescribed role of Nf1 in mammary collagen deposition and regulating adipocyte differentiation. In addition to unraveling the mechanism of tumor formation, further investigation of adipocytes and collagen modifications in preneoplastic mammary glands will create a foundation for developing early detection strategies of breast cancer among NF1 patients.